2008
DOI: 10.1136/adc.2007.128686
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of paediatric deaths due to myocarditis: an autopsy series

Abstract: Myocarditis is a rare cause of death in infancy and childhood, and the majority of cases present as sudden unexpected deaths, which require routine histological sampling of the heart for its detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…4,17,21,[23][24][25] The mean and median ages of patients with myocarditis were 5.4 and 5 years, respectively, which confirms that myocarditis is more likely to cause SUCD in older children. This is in accordance with the findings of Weber et al 25 In our series, conventional histopathological criteria were used to establish the diagnosis of myocarditis. 16,26 Reports have demonstrated limitations of the light-microscopy criteria (the Dallas criteria), pointing out that milder inflammatory changes may go undetected.…”
Section: Myocardial Disorderssupporting
confidence: 52%
“…4,17,21,[23][24][25] The mean and median ages of patients with myocarditis were 5.4 and 5 years, respectively, which confirms that myocarditis is more likely to cause SUCD in older children. This is in accordance with the findings of Weber et al 25 In our series, conventional histopathological criteria were used to establish the diagnosis of myocarditis. 16,26 Reports have demonstrated limitations of the light-microscopy criteria (the Dallas criteria), pointing out that milder inflammatory changes may go undetected.…”
Section: Myocardial Disorderssupporting
confidence: 52%
“…Myocarditis may present clinically with a range of symptoms and is increasingly implicated as a cause of sudden death in infancy and childhood. A recent study of autopsies in a United Kingdom hospital reported myocarditis as the cause of death in approximately 2% of the deaths of children Ͻ18 years old, 57% of which were sudden deaths (16,17).…”
Section: Case Reportmentioning
confidence: 99%
“…Of these, 5 infants were recruited from the MICU, 6 were recruited from the ICP, and 4 from the Inpatient Units. There were 10 males and 5 females with a median age of 2.0 (0.4-18) months, median weight of 5.8 (3)(4)(5)(6)(7)(8)(9)(10)(11) kg and median height of 60 (50-84) cm. Median time to acute stabilization was 4 (1-6) days, time between initial and final CO recording was 2.5 (0.8-7.2) days and length of hospitalization was 3.6 (1.6-8.9) days.…”
Section: Resultsmentioning
confidence: 99%
“…Infants with respiratory insufficiency from bronchiolitis may have similar clinical features to infants with congestive heart failure [7], presenting with irritability, fever, tachypnea, tachycardia and a mottled appearance. Although RSV infection seldom causes myocarditis, early detection of impaired cardiac output (CO) can be lifesaving in these infants [8] and similar to other etiologies for myocarditis may require emergent referral for advanced hemodynamic support (e.g., ECMO and heart [9,10]. Consequently, it is important to have the ability to monitor cardiac function in infants with RSV bronchiolitis in order to ensure optimal clinical management.…”
Section: Introductionmentioning
confidence: 99%